Age, sex, antihypertensive drugs and the Mediterranean diet on hypertension-related biomarkers: Impact on carotid structure and blood lipids in an Argentinian cross-sectional study - Georgina Noel Marchiori; Elio Andrés Soria; María Eugenia Pasqualini; María Alejandra Celi; María Daniela Defagó (Human Nutrition & Metabolism, 2024)
Background: Cardiovascular risk is modifiable by changes in lifestyle and pharmacological management, with hypertension being a common pathology worldwide. Its treatment must address multiple metabolic targets. Based on the hypothesis that certain antihypertensive medications, such as the commonly used enalapril and losartan, and dietary habits improve hypertension-related changes in carotid structure and cardiometabolic variables, this work aimed to associate these drugs, as well as the Mediterranean diet adherence and non-modifiable biological factors, with changes in carotid intima-media thickness [cIMT] and blood lipids. Methods: Sociodemographic, clinical, biochemical and lifestyle data were collected in a cross-sectional study of 313 subjects under survey due to cardiovascular risk factors, aged 34–83 years (Cordoba, Argentina). Generalised structural equation models were used for analysis. Results: A higher cIMT with age and male sex was confirmed. Women had lower triacylglycerols and saturated fatty acids in serum but higher circulating levels of LDL-C, HDL-C and total cholesterol than men. Also, a higher adherence to the Mediterranean diet was associated with lower triacylglycerols, but higher levels of HDL-C cholesterol and ω-3 polyunsaturated fatty acids (ω-3 PUFAs) in serum. A greater adherence to the Mediterranean diet did not affect cIMT. Enalapril was associated with increased serum ω-3 PUFAs levels, but it did not affect other lipid fractions. Moreover, enalapril may control cIMT, whereas losartan may not. Conclusions: Our data demonstrate that the Mediterranean diet and enalapril are associated with a cardioprotective circulating lipid profile in hypertension. Concerning this, enalapril potentially promotes serum ω-3 PUFAs levels beyond its classical antihypertensive effect, which encourages future clinical studies to confirm it.